The Effectiveness of Using the Digital Enrichment Platform (iQ) of the English Language Course (Skills for Success 1&2) in Developing Female Students’ Self-Learning Skills - Alharbi, Nawal N. (Journal of Ecohumanism, 2025)
This study aims to evaluate the effectiveness of using the digital enrichment (iQ) of the English language course (Skills for Success 1&2) at Applied Colleges in Al Qassim University in developing self-learning skills . So , the Reacher asks ‘ has the digital enrichment (iQ) of the English language course (Skills for Success) helped students to develop self-learning skills from their point of view?. To achieve the aim of the study, The experimental quantitative method in a quasi-experimental design was used in collecting data through the application of pre- and post-self learning scale. The sample was comprised of twenty female students and the data obtained from the study was analysed through a one sample t-test .The accuracy and reliability of the study tools were verified. The study revealed a high-level effect of using the digital enrichment platform (iQ) on the development of female students’ self-learning skills. There are statistically significant differences at a significance level of 0.05 between the pre-post questionnaire of the self-learning skills in favour of the post questionnaire. The study recommended using digital enrichment platforms in developing different skills.